Compound 48/80 acts as a potent mucosal adjuvant for vaccination against Streptococcus pneumoniae infection in young mice. Issue 8 (18th February 2015) - Zeng, Lingbin; Liu, Yusi; Wang, Hong; Liao, Pu; Song, Zhixin; Gao, Song; Wu, Yingying; Zhang, Xuemei; Yin, Yibing; Xu, Wenchun
Highlights: Immunization with C48/80 enhances and maintains antigen-specific IgG in serum of young mice. C48/80 helps to clear nasal pneumococcal colonization via B cells and IL-17A. C48/80 induces greater protection against lethal pneumococcal infection than CT. C48/80 is a relatively safe adjuvant for young mice. Abstract: Streptococcus pneumoniae, a major respiratory pathogen, is a leading cause of death among children worldwide. Mucosal vaccination is a recommended method to prevent respiratory infection. However, development of mucosal vaccination is usually hindered due to the lack of safe and effective mucosal adjuvants. Mast cell activator compound 48/80 (C48/80) has been used as a mucosal adjuvant in immunization of adult mice, but its adjuvanticity is not clear in the immunization of young mice. In this study, the adjuvanticity of C48/80 was evaluated when intranasally co-administrated with a pneumococcal vaccine candidate strain SPY1 in a young mice model in comparison with a classical mucosal adjuvant cholera toxin (CT) and a relatively safe mucosal adjuvant Pam2CSK4. All three adjuvants enhanced antibody responses, whereas serum IgG titers were maintained at a stable level during the 3 months after the last immunization only in the SPY1 + C48/80 and SPY1 + CT groups. Furthermore, both the SPY1 + CT group and the SPY1 + C48/80 group induced strong Th17 immune response. Notably, C48/80 showed the exceptional ability to promote the clearance of nasal pneumococcal colonization which CT and Pam2CSK4 did not show. We found that C48/80's ability to induce protection against nasal pneumococcal colonization depended on B cells and IL-17A. Additionally, C48/80, as a mucosal adjuvant, showed a greater ability to protect young mice against lethal pneumococcal infection than CT. In comparison with CT, C48/80 also showed a favorable safety. These results reveal a promising perspective for using C48/80 as a mucosal adjuvant to improve protection against pneumococcal diseases early in life.